MENGENAL ARTIFICIAL INTELLIGENCE DAN SISTEM PENGENALAN WAJAH UNTUK EDUKASI SISWA SMK FAJAR CISEENG - Nurhasanah; Nilovar Asyiah (Abdi Jurnal Publikasi, 2025)
This Community Service (PkM) activity aims to introduce the basic concepts of Artificial Intelligence (AI) and facial recognition systems to students of SMK Fajar Ciseeng. With the rapid advancement of technology, understanding AI and its implementation has become increasingly important, especially for secondary school students as the next generation in the digital era. The methods used in this activity include interactive material delivery, educational video presentations, facial recognition system simulations, and Q&A sessions. Students were provided with fundamental knowledge about how AI works, its benefits in daily life, and the application of facial recognition systems in various fields, such as security and education. The results of this activity show that students demonstrated high enthusiasm and were able to grasp the basic concepts of AI and the working mechanism of facial recognition systems. The outcome of this program is expected to foster students’ interest in the field of information technology and encourage schools to begin integrating AI-based technology learning into the curriculum.